Формування інформаційної бази оцінювання економічної безпеки будівельних підприємств - Зіненко, Костянтин Анатолійович (Національний технічний університет "Харківський політехнічний інститут", 2022)
Метою статті є дослідження теоретико-методичних та практичних засад інформаційного забезпечення процесів оцінювання та забезпечення необхідного рівня економічної безпеки будівельних підприємства. В статті доведено, що для проведення якісного оцінювання економічної безпеки підприємства будівельної галузі та отримання достовірних оцінок про її рівень, необхідно створити якісну інформаційну базу оцінювання та зібрати набір даних які виражаються показниками діяльності. Вони мають бути сформовані відповідно обраної моделі подання інформації яка відображає в упорядкованому вигляді господарські процеси і явища, які відбуваються та є сукупністю даних про них. Обґрунтовано, що для проведення якісного оцінювання економічної безпеки підприємства будівельної галузі та отримання достовірних оцінок про її рівень необхідно створити якісну інформаційну базу оцінювання та зібрати набір інформаційних даних які виражаються показниками діяльності. Вони мають бути сформовані відповідно обраної моделі подання інформації яка відображає в упорядкованому вигляді господарські процеси і явища, які відбуваються та є сукупністю даних про них. Для формування інформаційної бази оцінювання економічної безпеки будівельного підприємства, на основі отриманих результатів якого будуть прийматися рішення щодо її забезпечення, запропоновано застосувати системний підхід, який базується на наступному розподілі елементів: структуруванні економічної безпеки за складовими за якими визначається рівень безпеки й структуровані інтересів та чинників впливу за групами стейкхолдерів відповідно представленої системи і методики оцінювання де рівень економічної безпеки визначається з урахуванням інтересів та чинників впливу на економічну безпеку за групами стейкхолдерів, які виражені у якісних показниках, що визначені експертним методом та досліджені у динаміці. Кількісні (показники економічної безпеки за складовими) і якісні показники (інтереси підприємства, чинники впливу), є вимірюванням досяжності цілі, де в основу побудови інформаційної бази на основі системного підходу покладено загальне поняття мети – визначення комплексного інтегрального показника, який достовірно відтворює сучасний стан економічної безпеки будівельного підприємства. Представлено інформаційну бази для оцінювання економічної безпеки підприємства у вигляді геометричної інтерпретації як простору з визначеною кількістю векторів, які відповідатимуть складовим економічної безпеки підприємства та групам стейкхолдерів за якими визначені інтереси та чинники впливу надає можливість формування якісної інформаційної бази для якісного та достовірного оцінювання економічної безпеки будівельного підприємства.

The purpose of the article is to study the theoretical, methodological and practical foundations of information support for assessment processes and ensuring the necessary level of economic security of construction enterprises. The article proves that in order to carry out a qualitative assessment of the economic security of an enterprise in the construction industry and obtain reliable estimates of its level, it is necessary to create a high-quality informational assessment base and collect a set of data expressed by performance indicators. They should be formed in accordance with the chosen model of information presentation, which reflects in an orderly form the economic processes and phenomena that occur and is a collection of data about them. It is substantiated that in order to carry out a qualitative assessment of the economic security of a construction industry enterprise and obtain reliable assessments of its level, in our opinion, it is necessary to create a qualitative information base for assessment and collect a set of information data expressed by performance indicators. They should be formed in accordance with the selected information presentation model that reflects in an orderly form the economic processes and phenomena that occur and is a collection of data about them. In order to form an information base for assessing the economic security of a construction enterprise, based on the results of which decisions will be made regarding its provision, it is proposed to apply a systematic approach based on the following distribution of elements: the structuring of economic security according to the components by which the level of security is determined and structured by interests and influencing factors according to the stakeholder groups of the correspondingly presented assessment system and methodology, where the level of economic security is determined taking into account the interests and factors of influence on economic security according to the stakeholder groups, which are expressed in qualitative indicators determined by the expert method and studied in dynamics. Quantitative (indicators of economic security by components) and qualitative indicators (interests of the enterprise, factors of influence) are a measure of the achievement of the goal, where the construction of an information base based on a systemic approach is based on the general concept of the goal - the definition of a complex integral indicator that reliably reproduces the current state of the economic safety of the construction enterprise. An information base for assessing the economic security of the enterprise is presented in the form of a geometric interpretation as a space with a certain number of vectors that will correspond to the components of the economic security of the enterprise and groups of stakeholders whose interests and influence factors are determined, which makes it possible to form a high-quality information base for a high-quality and reliable assessment of the economic security of a construction enterprise.
Formation of the information base for evaluating the economic security of construction enterprises
Keywords: інформація; інформаційне забезпечення; економічна безпека; чинники впливу; стейкхолдери; будівельне підприємство; information; information support; economic security; influencing factors; stakeholders; construction enterprise